A longitudinal perspective on behavioral outcomes of preterm children: looking beyond composite scales - Meijer, Julia S.; Leenen, Sanne; Vugs, Brigitte; Van Beek, Pauline; Van Pul, Carola; Andriessen, Peter (Frontiers in Developmental Psychology, 2026)
IntroductionThis study aimed to evaluate parental perspectives on behavioral development in preterm children over time, and to evaluate the impact of adverse early life events on multiple domains of behavior.MethodsSingle-center cohort study (January 2010 – December 2016) including children born between 24 and 30 weeks' gestation. Behavior was investigated using the Child Behavior Checklist (CBCL) at 2, 5.5 and 8 years' corrected age. As a proxy of adverse early life events, we used a binary composite measure indicating the presence of any of the following: postnatal corticosteroid administration, perinatal brain injury, surgical interventions or prolonged ventilation. Linear mixed model analysis was used to explore behavioral development over time and associations with adverse early life events.ResultsIn total, 204 children had CBCL assessments at all ages. Attention problems (20%) and anxious-depressed (13%) behavior showed the highest clinically relevant scores and steepest increase over time, respectively. Exposure to adverse early life events was associated with attention problems and withdrawn behaviors.DiscussionSubscale-level evaluation characterizes the behavioral phenotype of preterm children and shows a progressive increase in difficulties over time. Exposure to adverse early life events is associated with increased problems across multiple behavioral domains. Identifying at-risk children may facilitate accurate monitoring and targeted intervention.